Structure and Properties of Aluminium Alloys - Zupanič, Franc (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The demand for aluminum alloys is increasing because of their lightness, high specific strength and other attractive properties, which can exploited in improved products for a greener environment. This book gives a correlation between the processing, microstructure and properties of several aluminium alloys. Some of them are well established and used in an enormous number of applications, while others are still under development. The processing spans from casting, rapid solidification, additive manufacturing, forming, heat-treatment and welding, which can produce interesting microstructures and a useful combination of properties.